1998
DOI: 10.1002/(sici)1096-9861(19980112)390:2<247::aid-cne7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of synapses in the lateral geniculate nucleus of the cat: Differences between laminae A and A1 and between relay cells and interneurons

Abstract: Laminae A and A1 of the lateral geniculate nucleus in the cat are generally considered to be a structurally and functionally matched pair of inputs from two eyes, although there are subtle light microscopic and physiological differences. The present study aims to display ultrastructural differences between these two laminae based on electron microscopic observances on the connectivity patterns of their afferents onto two main cell types: relay cells, and interneurons present in this nucleus. In a design of pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…In comparison to RL corticothalamic terminals, which contacted very few interneurons (2%), we found that interneurons comprised 26% of the postsynaptic targets of retinal terminals. This distribution is similar to the contacts of retinogeniculate terminals in the cat (31.2%; Erisir et al, 1998). Thus, in both the rat and cat a substantial fraction of the synaptic targets of retinogeniculate terminals are interneurons.…”
Section: Discussionsupporting
confidence: 78%
“…In comparison to RL corticothalamic terminals, which contacted very few interneurons (2%), we found that interneurons comprised 26% of the postsynaptic targets of retinal terminals. This distribution is similar to the contacts of retinogeniculate terminals in the cat (31.2%; Erisir et al, 1998). Thus, in both the rat and cat a substantial fraction of the synaptic targets of retinogeniculate terminals are interneurons.…”
Section: Discussionsupporting
confidence: 78%
“…7). Although in visual, auditory, and somatosensory thalamic nuclei, principal sensory relay cells also receive their primary input at large-caliber, presumably proximal, dendrite segments (Liu et al, 1995;Erisir et al, 1998;Bartlett et al, 2000;Guillery and Sherman, 2002), highly exclusive and invasive targeting of initial dendrite segments of gustatory thalamic cells is unique to the gustatory system.…”
Section: Parabrachiothalamic Input To the Vpmpcmentioning
confidence: 99%
“…In the cat, the GABA immunoreactive F terminals represent inhibitory inputs from local interneurons and neurons of the thalamic reticular nucleus (TRN) [15,[40][41][42][43][44][45][46][47]. However, in the rat, the thalamic nuclei other than the LGN lack interneurons [43,44].…”
Section: The F Synaptic Junctionsmentioning
confidence: 99%